ANALISIS KOMPARATIF USAHATANI PADI LADANG DAN JAGUNG DI DESA TANJUNG SARI KECAMATAN BLAMBANGAN UMPU KABUPATEN WAY KANAN (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2017)
This research is about comparative analysis of farming of rice field and maize in Desa Tanjung Sari Blambangan Umpu District of Way Kanan Regency. The result of this research is the income of paddy field farming is bigger compared to the income of corn farming business in Desa Tanjung Sari Blambangan Umpu District of Way Kanan Regency. Based on calculation result got value of R / C ratio> 1 at farming paddy field equal to 1,35. This means that every one-unit cost incurred by farmers receives revenue of 1.35 times per hectare per year. This shows that the rice field business is feasible to bring profits or income for farmers. Then the value of R / C ratio> 1 on the farming of paddy fields of 1.37. This means every one-unit cost incurred farmers earn receipts of 1.37 times per hectare per year. This shows that corn business is feasible to bring profits or income for farmers. Based on the results of hypothesis testing on the comparison of farming income of paddy fields and maize of Tanjung Sari Village Blambangan Umpu District Way Kanan Regency obtained t-count as big as 0,652 ≤ t-table at α = 0,05 (2,145). This means that the income of paddy field farming and maize of Tanjung Sari Village Blambangan Umpu District of Way Kanan Regency is significantly different.